Cardiofacialcutaneous syndrome. Case report. - Alqubaisy, Y.; Alkhalifah, Y. (European Journal of Pediatric Dermatology, 2016)
A 15-year-old boy affected by alopecia areata of the eyebrows and wooly hair presented many dysmorphic features, congenital heart defect and dry skin. He had a history of delayed milestones and low borderline IQ. He was clinically diagnosed with cardiofaciocutaneous syndrome. The features of cardiofaciocutaneous syndrome and its dermatological findings were discussed.